ANALISIS SISTEM PENDIDIKAN ZAMAN JEPANG DI INDONESIA : DARI PENYERANGAN SEKOLAH HINGGA PENANAMAN JIWA MILITER - Nilam Sari (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2026)
The Japanese occupation of Indonesia (1942–1945) brought significant changes to the education system, from the standardization of schools to the instillation of military values and loyalty to the Japanese Emperor. The discriminatory Dutch colonial system was abolished and replaced with a simpler, centralized education focused on discipline, ideological indoctrination, and semi-military training through organizations such as Seinendan, Keibodan, Heiho, and PETA. Although Japanese education primarily aimed to support the war effort and propaganda, the organizational experience and military training indirectly fostered national awareness and prepared Indonesian youth for the struggle for independence. Thus, Japanese-era education was both repressive and strategic in shaping national identity and strength.